THE HYBRID DYSTOPIA MODEL: AN ORWELLIAN-HUXLEYAN READING OF SOCIAL MEDIA THROUGH NINETEEN EIGHTY-FOUR AND BRAVE NEW WORLD - Otabek Tillaev (International Journal of Literature and Language Studies, 2026)
With the development of digital communication technologies, social media platforms have transformed from digital environments in which individuals communicate only to complex sociotechnical systems in which behaviors are analyzed, attention is managed and social interactions are reshaped. This study aims to examine the functioning of social media platforms comparatively in the axis of George Orwell's 1984 and Aldous Huxley's Brave New World novels. The research was conducted on the basis of document review from qualitative research methods and comparative literary analysis approach. In the study, Orwell's 1984 novel was evaluated in the context of algorithmic surveillance, data collection, digital control, propaganda and information manipulation that constitute the technical infrastructure of social media; Huxley's Brave New World novel was analyzed within the framework of attention economy, personalized content, pleasure-oriented user experience, consumption culture and digital alienation. The research findings reveal that social media platforms cannot be explained through a single dystopian model. The platforms' data collection processes, algorithmic decision-making mechanisms, and behavior prediction systems create a digital control structure in which individuals are constantly monitored, while the user experience exhibits a pleasure-oriented structure that encourages voluntary participation through entertainment, personalization, short video culture, appreciation mechanisms, and continuous interaction. In this direction, social media is considered as a multi-layered system that produces both digital surveillance and attention economy at the same time. To sum up, the study reveals that the technical architecture of social media is remarkably similar to the surveillance society posed by Orwell, while the logic of content production and user experience are significantly similar to the pleasure-centered social order depicted by Huxley. These findings indicate that contemporary social media platforms embody not only the surveillance and algorithmic control envisioned by Orwell but also the entertainment-driven culture, consumerism, and voluntary compliance anticipated by Huxley. Building on this analysis, the study proposes a novel conceptual framework, the Hybrid Dystopia Model, which explains how power on digital platforms operates simultaneously through technical surveillance and content-driven consent. Unlike previous studies that interpret social media through either an Orwellian or a Huxleyan perspective, this model demonstrates that both forms of power coexist and reinforce one another within contemporary digital platforms. By integrating Orwellian and Huxleyan perspectives into a single analytical framework, the proposed model offers a new theoretical lens for understanding governance, user behavior, and algorithmic power in the age of social media.